2019
DOI: 10.4025/actascitechnol.v41i1.39693
|View full text |Cite
|
Sign up to set email alerts
|

Screening of fungal strains with potentiality to hydrolyze microalgal biomass by Fourier Transform Infrared Spectroscopy (FTIR)

Abstract: The use of fungi is a promising alternative for harnessing biomass after lipid extraction of microalgae since this biomass may contain relevant levels of carbohydrates that can be converted into other compounds of interest, such as sugars. Fourier Transform Infrared Spectroscopy (FTIR) has proved to be an efficient and environmentally less impacting tool for the selection of microorganisms with biotechnological potential. This study aimed to apply FTIR for the selection of fungal strains with potential to hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Resende et al (2002), using the same strain, demonstrated the production of xylanase and cellulase in sugarcane bagasse fermentation under solid-state conditions, with the average yield of xylanase being higher than that of cellulose. This feature is shared by other Trichoderma species (De Souza, et al, 2019). Thus, considering that L. cylindrica bushing is chemically composed of cellulose (65.2%), hemicellulose (17.5%), and lignin (15.2%) (Siqueira et al, 2010), it is possible to suggest that the biodegradability of the plant support occurred through the action of the xylanase produced by the fungus.…”
Section: Immobilization Of Filamentous Fungus In Synthetic and Natura...mentioning
confidence: 99%
“…Resende et al (2002), using the same strain, demonstrated the production of xylanase and cellulase in sugarcane bagasse fermentation under solid-state conditions, with the average yield of xylanase being higher than that of cellulose. This feature is shared by other Trichoderma species (De Souza, et al, 2019). Thus, considering that L. cylindrica bushing is chemically composed of cellulose (65.2%), hemicellulose (17.5%), and lignin (15.2%) (Siqueira et al, 2010), it is possible to suggest that the biodegradability of the plant support occurred through the action of the xylanase produced by the fungus.…”
Section: Immobilization Of Filamentous Fungus In Synthetic and Natura...mentioning
confidence: 99%